2006
DOI: 10.1139/f05-233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reservoir connectivity on stream fish assemblages in the Great Plains

Abstract: The upstream effects of reservoirs on stream fish assemblages were highly localized in 3rd-through 5th-order streams in the Great Plains, USA. Streams that differed in connectivity to reservoirs were sampled at their confluences with a river or reservoir and between the confluence and the stream's origin. Sites at confluences had higher total, nonnative, and reservoir species richness than middle sites. Variability in fish assemblage structure upstream of reservoirs was influenced by catchment area, stream siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 33 publications
3
36
0
Order By: Relevance
“…Although we are unaware of any previous investigations of fish diversity within delta habitats, our results are similar to a study conducted on plants wherein plant diversity was higher within delta habitats than reservoirs (Johnson, 2002). Moreover, Falke and Gido (2006) found higher fish species richness at the confluence of tributary streams with reservoirs than in the tributary streams themselves. These confluence habitats may be similar to the Niobrara River delta.…”
Section: Discussionsupporting
confidence: 85%
“…Although we are unaware of any previous investigations of fish diversity within delta habitats, our results are similar to a study conducted on plants wherein plant diversity was higher within delta habitats than reservoirs (Johnson, 2002). Moreover, Falke and Gido (2006) found higher fish species richness at the confluence of tributary streams with reservoirs than in the tributary streams themselves. These confluence habitats may be similar to the Niobrara River delta.…”
Section: Discussionsupporting
confidence: 85%
“…Smith and Kraft (2005) also found that confluence link (watershed size of stream segments immediately downstream of sites) was a significant predictor of fish assemblage structure in the Beaverkill-Willowemoc watershed in New York. Similarly, Falke and Gido (2006a) showed that confluence sites between streams and reservoirs (i.e., stream sites within the floodplain of the reservoir) had higher total nonnative and reservoir species richness than sites 4-16 km upstream of those confluences, suggesting a localized effect of reservoirs. Close proximity to a large river also can influence variability of stream fish assemblages, as sites closer to interface zones were found to be more temporally variable in an adventitious Illinois stream than sites more distant to those interfaces (Schaefer and Kerfoot 2004).…”
Section: Introductionmentioning
confidence: 91%
“…in Ken River support great variety of fauna (Kaemingk et al 2007). Moreover, it is a well established fact that there is occurrence of higher species richness at the confluence of tributary streams with the main river than in the tributary streams (Falke & Gido 2006). Further, the low diversity of fish documented in streams associated with Ken River is mainly due to the drying of streams during summer.…”
Section: Discussionmentioning
confidence: 98%